NUMERICAL AND ANALYTICAL ANALYSIS OF THE SHAFT DESIGN FOR A ROTATING DRUM BIOREACTOR USING STAINLESS STEEL 304 MATERIAL - Putero, Gladion Alim; Affandy, Rahmat; Fauzi, Mochamad; Zain, Fikri Isya; Prabawanto, Moch. Nur Irsyad; Faizin, Ahmad Khairul (Universitas Muhammadiyah Surakarta, 2025)
The safety factor and Von Mises stress need to be analyzed so that the components remain safe against combined stress and the risk of failure due to dynamic loads and unexpected conditions. This study aims to analyze the safety factor and von mises of the shaft design on a rotating drum bioreactor using 304 stainless steel material. This machine is designed to support the shrimp paste fermentation process using the Solid State Fermentation (SSF) method. The analysis process is carried out through simulation using the finite element method (FEM) to evaluate the stress distribution and safety factor value on the shaft. The simulation results show that the von mises value or maximum stress on the shaft is 10.98 N/mm², still below the yield strength of 304 stainless steel material of 205 N/mm². The minimum safety factor obtained from the analysis is 19, indicating that this design is safe to withstand loads during the operation process. In addition, the results of the numerical analysis using manual calculations obtained a maximum shaft stress value of 10.95 N/mm² with a minimum safety factor value of 18.7. Through a comparison of the results of the analytical simulation analysis and manual numerical calculations, a machine design with a level of reliability and structural safety that is considered safe, as well as minimizing the risk of mechanical failure.